Preservation of circadian rhythms by the protein folding chaperone, BiP. Issue 6 (19th March 2019) - Pickard, Adam; Chang, Joan; Alachkar, Nissrin; Calverley, Ben; Garva, Richa; Arvan, Peter; Meng, Qing-Jun; Kadler, Karl E.
ABSTRACT: Dysregulation of collagen synthesis is associated with disease progression in cancer and fibrosis. Collagen synthesis is coordinated with the circadian clock, which in cancer cells is, curiously, deregulated by endoplasmic reticulum (ER) stress. We hypothesized interplay between circadian rhythm, collagen synthesis, and ER stress in normal cells. Here we show that fibroblasts with ER stress lack circadian rhythms in gene expression upon clock‐synchronizing time cues. Overexpression of binding immunoglobulin protein (BiP) or treatment with chemical chaperones strengthens the oscillation amplitude of circadian rhythms. The significance of these findings was explored in tendon, where we showed that BiP expression is ramped preemptively prior to a surge in collagen synthesis at night, thereby preventing protein misfolding and ER stress. In turn, this forestalls activation of the unfolded protein response in order for circadian rhythms to be maintained. Thus, targeting ER stress could be used to modulate circadian rhythm and restore collagen homeostasis in disease.—Pickard, A., Chang, J., Alachkar, N., Calverley, B., Garva, R., Arvan, P., Meng, Q.‐J., Kadler, K. E. Preservation of circadian rhythms by the protein folding chaperone, BiP. FASEB J. 33, 000–000 (2019). www.fasebj.org